Great Eurasia: Civilizational Space and Designing the Future - Igor F. Kefeli (Евразийская интеграция: экономика, право, политика, 2019)
The notion of Big Eurasia included in scientific and political lexicon is relatively recent and rapidly filled with new content. Awakening public interest in the Eurasianism coincided with the objective trend of integration States that emerged in Eurasia after the collapse of the Soviet Union. Offensive Antropocene as new geological epoch and global developments Eurasia’s «geopolitical plates», the industrial revolution 4.0 and the resultant feeling of «life in the crumbles world» fundamentally change the inner world of man, power over which all more tightly beginning to capture mechanisms to algorithmization of conduct and Artificial Intelligence. Projective function Big Eurasia as ideological and theoretical construct is implemented in the policy documents and contracts for coalitions of States of the continent on a mezhcivilizacionnoj basis.